Studying Autism Spectrum Disorder with Structural and Diffusion Magnetic Resonance Imaging: A Survey - Marwa Maher Tawfik Ismail; Robert S. Keynton; Mahmoud Mohamed Mahmoud Osman Mostapha; Ahmed Hazem ElTanboly; Manuel Fernando Casanova; Georgy L Gimel'farb; Ayman eEl-Baz (Frontiers in Human Neuroscience, 2016)
Magnetic resonance imaging (MRI) modalities have emerged as powerful means that facilitatenon-invasive clinical diagnostics of various diseases and abnormalities since their inception in the1980s. Multiple MRI modalities, such as different types of the sMRI and DTI, have been employedto investigate facets of ASD in order to better understand this complex syndrome. This paperreviews recent applications of structural magnetic resonance imaging (sMRI) and diffusion tensorimaging (DTI), to study autism spectrum disorder (ASD). Main reported findings are sometimescontradictory due to different age ranges, hardware protocols, population types, numbers of participants,and image analysis parameters. The primary anatomical structures, such as amygdalae,cerebrum, and cerebellum, associated with clinical-pathological correlates of ASD are highlightedthrough successive life stages, from infancy to adulthood. This survey demonstrates the absenceof consistent pathology in the brains of autistic children and lack of research investigations in patientsunder two years of age in the literature. The known publications also emphasize advancesin data acquisition and analysis, as well as significance of multimodal approaches that combineresting-state, task-evoked, and sMRI measures. Initial results obtained with the sMRI and DTIshow good promise towards the early and non-invasive ASD diagnostics.